EFEKTIVITAS PENGAPLIKASIAN PUPUK ORGANIK CAIR TERHADAP TINGKAT SERANGAN HAMA DAN PENYAKIT TANAMAN CABAI KERITING (Capsicum annuum L.) - Wati, Cheppy; Sulistyowati, Dwiwanti; Krisnawati, Endang (Fruitset Sains : Jurnal Pertanian Agroteknologi, 2025)
Curly chili (Capsicum annuum L.) is a horticultural commodity of significant economic value in Indonesia. However, its production frequently encounters challenges due to pests and diseases.This study aims to examine the effectiveness of liquid organic fertilizer (POC) in mitigating pest and disease attacks on curly chili plants. The study was conducted from March to December 2024 at the Experimental Garden of the Department of Agriculture, Bogor Agricultural Development Polytechnic.The experiment employed a nested plot design, incorporating two levels of NPK fertiliser application and three levels of POC doses.The parameters observed encompassed the population of the primary pests, the presence of natural enemies, and the incidence of the predominant diseases. The findings indicated that the application of POC at optimal doses was effective in suppressing pest populations and reducing the incidence of diseases, particularly Cucumber Mosaic Virus (CMV) (10.69%) and Pepper Yellow Leaf Curl Virus (13.97%).Consequently, the study concluded that the application of POC holds considerable potential as an environmentally sustainable alternative in the curly chili cultivation system, thereby reducing reliance on chemical pesticides.